UJI AKTIVITAS ANTIBAKTERI DAN SKRINING FITOKIMIA EKSTRAK HEKSANA, ETIL ASETAT DAN METANOL TUMBUHAN SURUHAN (Peperomia pellucida L. Kunth) - Restianti Restianti; Bimo Budi Santoso; Maria Ludya Pulung (FMIPA Universitas Papua, 2020)
Antibacterial activity test and screening of phytochemical of extract hexane, ethyl acetate and methanol have been carried out. The extraction of the P.pellucida plants was carried out by the maceration method in stages based on the polarity of the solvent. Analysis of chemical compounds done with phytochemical screening test. Based on the identification of chemical compounds by phytochemical screening, hexane and ethyl acetate extract has been detected only in the presence of flavonoid compounds with moderate categories. Methanol extract contains high-grade alkaloids and moderate flavonoid and tannin compounds. Antibacterial test using disffusion methods suggest that ethyl acetate and methanol extract have categorically strong antibacterial activity againts the S. aureus of 14 mm and 16 mm respectively. Hexane extract and acetate ethyl have a strong inhibition to E. coli of 11 mm and 12 mm respectively. Methanol extract has a weak inhibition to bacteria E. coli and a hexane extract has a weak inhibition to bacteria S. aureus.